Component Certification as a Prerequisite forWidespread OSS Reuse - Kakarontzas, George; Katsaros, Panagiotis; Stamelos, Ioannis (Electronic Communications of the EASST, 2010)
Open source software is the product of a community process that in a single project may employ different development techniques and volunteers with diverse skills, interests and hardware. Reuse of OSS software in systems that will have to guarantee certain product properties is still complicated. The main reason is the many different levels of trust that can be placed on the various OSS sources and the lack of information for the impact that a reused OSS component can have on the system properties. A prerequisite for promoting widespread reuse of OSS software is certification at the component level in an affordable cost. This work addresses the main technical issues behind OSS component certification by formal and semiformal techniques, as well as the incentives that raised the need for the OPEN-SME European funded project. OPEN-SME introduces an OSS software reuse service for SMEs, in order to address the problem that OSS evolves by volunteers that follow different development processes. We discuss the requirements relating to OSS software reuse based on the findings of a survey. Then we present the OPEN-SME tool-set and approach for OSS reuse and finally we show how the provision of verifiable certificates can provide assurance that an OSS component conforms to one or more anticipated requirements, necessary for reusing it in a system.